Termite Resistant Properties of Sisal Fiberboards - Firda Aulya Syamani; Muhamad Yusram Massijaya; Bambang Subiyanto (Insects, 2011)
A study was carried out to test sisal (Agave sisalana Perrine) fiberboards properties as building materials against Asian subterranean termite, Coptotermes gestroi (Wasmann). Evaluation was in the laboratory according to the JWPA Standard-TW-S.1-1992. To improve mechanical properties of fiberboards made from sisal fibers, the boards were overlaid by rubber veneer, betung bamboo matting or formica. Result showed that the formica-overlaid sisal fiberboards performed better than other overlaid fiberboards against C. gestroi.